Structure activity related, mechanistic, and modeling studies of gallotannins containing a glucitol-core and α-glucosidase. Issue 130 (21st December 2015) - Ma, Hang; Wang, Ling; Niesen, Daniel B.; Cai, Ang; Cho, Bongsup P.; Tan, Wen; Gu, Qiong; Xu, Jun; Seeram, Navindra P.
Abstract : Evaluation of the mechanisms of inhibitory activities of gallotannins containing a glucitol core (GCGs) on α-glucosidase. Abstract : Gallotannins containing a glucitol core, which are only produced by members of the maple ( Acer ) genus, are more potent α-glucosidase inhibitors than the clinical drug, acarbose. While this activity is influenced by the number of substituents on the glucitol core ( e.g. more galloyl groups leads to increased activity), the mechanisms of inhibitory action are not known. Herein, we investigated ligand–enzyme interactions and binding mechanisms of a series of 'glucitol-core containing gallotannins (GCGs)' against the α-glucosidase enzyme. The GCGs included ginnalins A, B and C (containing two, one, and one galloyl/s, respectively), maplexin F (containing 3 galloyls) and maplexin J (containing 4 galloyls). All of the GCGs were noncompetitive inhibitors of α-glucosidase and their interactions with the enzyme were further explored using biophysical and spectroscopic measurements. Thermodynamic parameters (by isothermal titration calorimetry) revealed a 1 : 1 binding ratio between GCGs and α-glucosidase. The binding regions between the GCGs and α-glucosidase, probed by a fluorescent tag, 1, 1′-bis(4-anilino-5-naphthalenesulfonic acid), revealed that the GCGs decreased the hydrophobic surface of the enzyme. In addition, circular dichroism analyses showed that the GCGs bind to α-glucosidase and lead to loss of the secondary α-helix structure of the protein. Also, molecular modeling was used to predict the binding site between the GCGs and the α-glucosidase enzyme. This is the first study to evaluate the mechanisms of inhibitory activities of gallotannins containing a glucitol core on α-glucosidase.